Eye Contact Is a Two-Way Street: Arousal Is Elicited by the Sending and Receiving of Eye Gaze Information - Jarick, Michelle; Bencic, Renee (Frontiers in Psychology, 2019)
Research shows that arousal is significantly enhanced while participants make eye contact with a live person compared to viewing a picture of direct or averted gaze. Recent research has pointed toward the potential for social interaction as a possible driving force behind the arousal enhancement. That is, eye gaze is not only a signal perceived but also a signal sent out in order to communicate with others. This study aimed to test this by having dyads engage in eye contact and averted gaze naturally, while wearing sunglasses, and while blindfolded; such that the gaze signals were clear, degraded, and blocked, respectively. Autonomic nervous system arousal was measured via skin conductance response and level. The results showed that dyads exhibited the highest degree of arousal (increased skin conductance) while making eye contact (send/receive) compared to send-only or receive-only gaze trials; however, this was only the case if eye contact was clear. Once gaze information became degraded (by sunglasses or blindfold), arousal significantly decreased and was no longer modulated by the sending and receiving of gaze. Therefore, the arousal enhancement observed during eye contact is not only caused by receiving gaze signals (the focus of previous research) and should be more accurately attributed to the subtle interplay between sending and receiving gaze signals.